2016
DOI: 10.1007/s12593-014-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Cognitive Flexibility with Pain Intensity and Magnitude of Disability in Upper Extremity Illness

Abstract: Cognitive flexibility -the ability to restructure one's knowledge, incorporate new facts, widen perspective, and adapt to the demands of new and unexpected conditionscan help one adapt to illness. The aim of this study was to assess the relationship between cognitive flexibility and hand and upper extremity specific disability in patients presenting to a hand surgeon. Secondarily, we determined predictors of cognitive flexibility and pain. Eighty-nine consecutive outpatients completed the Cognitive flexibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
3
19
1
Order By: Relevance
“…Our study also confirms prior research on the relationship of psychological inflexibility to both depression and anxiety, of depression and anxiety to pain intensity, and of anxiety to upper extremity physical function . However, neither depression nor anxiety were supported as mediators when entered together with pain catastrophizing in the mediation models, suggesting that only pain catastrophizing carries the effect of psychological inflexibility on pain and upper extremity physical function in patients with musculoskeletal pain.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study also confirms prior research on the relationship of psychological inflexibility to both depression and anxiety, of depression and anxiety to pain intensity, and of anxiety to upper extremity physical function . However, neither depression nor anxiety were supported as mediators when entered together with pain catastrophizing in the mediation models, suggesting that only pain catastrophizing carries the effect of psychological inflexibility on pain and upper extremity physical function in patients with musculoskeletal pain.…”
Section: Discussionsupporting
confidence: 87%
“…A second goal of this study is to test potential mechanisms of development of pain and upper extremity physical function in this population. Prior research in this population has shown the pivotal roles of pain catastrophizing, anxiety, and depression in reports of pain intensity and upper extremity disability, but the relationships of a general construct of psychological inflexibility to pain catastrophizing, anxiety, and depression in patients with musculoskeletal pain in orthopedic surgical practices have not been studied. We propose that psychological inflexibility will impact pain intensity and upper extremity physical function both directly, as well as indirectly through increased pain catastrophizing, depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to prolong cast immobilization is often influenced by pain during physical examination, fracture tenderness in particular. Evidence has established a considerable influence of emotions and cognitive bias on pain intensity and magnitude of physical limitations (Gruber et al., 2014; Hadlandsmyth et al., 2017; Hageman et al., 2014; Kortlever et al., 2015; Nota et al., 2015; Oh et al., 2017; Ozkan et al., 2017; Ring et al., 2006; Vranceanu et al., 2014). People feel better and can do more when they accurately interpret symptoms and feel secure and hopeful.…”
Section: Discussionmentioning
confidence: 99%
“…Pain intensity varies substantially for a given signal entering the central nervous system after stimulation of sensory receptors (nociception) (Institute of Medicine (US) Committee on Pain, Disability, and Chronic Illness Behavior, 1987; Menendez and Ring, 2016). This variation in pain intensity is largely determined by stress, distress and cognitive bias regarding pain (Gruber et al., 2014; Hadlandsmyth et al., 2017; Hageman et al., 2014; Kortlever et al., 2015; Ozkan et al., 2017; Ring et al., 2006; Vranceanu et al., 2014). For instance, patients with greater levels of catastrophic (worst-case) thinking tend to experience more pain (Darnall, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…18 The finding that lower magnitude of physical limitations was independently associated with greater self-efficacy and greater pain intensity was associated with greater catastrophic thinking and lower self-efficacy is in line with previous evidence. 15,[20][21][22] There is consistent and extensive evidence that psychological factors-effective coping strategies such as self-efficacy and ineffective strategies such as catastrophic thinking in particular-account for a large portion (often the majority) of the magnitude of physical limitations and pain intensity for several specific and nonspecific upper extremity conditions. [23][24][25] Greater satisfaction with the visit was independently associated with greater self-efficacy.…”
Section: Discussionmentioning
confidence: 99%